Human papillomavirus E6 protein enriches the CD55(+) population in cervical cancer cells, promoting radioresistance and cancer aggressiveness - Leung, Thomas Ho‐Yin; Tang, Hermit Wai‐Man; Siu, Michelle Kwan‐Yee; Chan, David Wai; Chan, Karen Kar‐Loen; Cheung, Annie Nga‐Yin; Ngan, Hextan Yuen‐Sheung (The Journal of pathology, 2018)
Accumulating evidence indicates that the human papillomavirus (HPV) E6 protein plays a crucial role in the development of cervical cancer. Subpopulations of cells that reside within tumours are responsible for tumour resistance to cancer therapy and recurrence. However, the identity of such cells residing in cervical cancer and their relationship with the HPV‐E6 protein have not been identified. Here, we isolated sphere‐forming cells, which showed self‐renewal ability, from primary cervical tumours. Gene expression profiling revealed that cluster of differentiation (CD) 55 was upregulated in primary cervical cancer sphere cells. Flow‐cytometric analysis detected abundant CD55(+) populations among a panel of HPV‐positive cervical cancer cell lines, whereas few CD55(+) cells were found in HPV‐negative cervical cancer and normal cervical epithelial cell lines. The CD55(+) subpopulation isolated from the C33A cell line showed significant sphere‐forming ability and enhanced tumourigenicity, cell migration, and radioresistance. In contrast, the suppression of CD55 in HPV‐positive CaSki cells inhibited tumourigenicity both in vitro and in vivo, and sensitized cells to radiation treatment. In addition, ectopic expression of the HPV‐E6 protein in HPV‐negative cervical cancer cells dramatically enriched the CD55(+) subpopulation. CRISPR/Cas9 knockout of CD55 in an HPV‐E6‐overexpressing stable clone abolished the tumourigenic effects of the HPV‐E6 protein. Taken together, our data suggest that HPV‐E6 protein expression enriches the CD55(+) population, which contributes to tumourigenicity and radioresistance in cervical cancer cells. Targeting CD55 via CRISPR/Cas9 may represent a novel avenue for developing new strategies and effective therapies for the treatment of cervical cancer. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.